Main Tasks of Realisation of the Programme of Informatisation of a Higher Educational Establishment Основные задачи реализации программы информатизации высшего учебного заведения - Tsohla Svitlana Yu.; Burlay Mykhaylo M. (Bìznes Inform, 2013)
The article studies factors of competitiveness of an educational establishment: demand on specialties, their popularity and cost of education. The conducted analysis showed that these factors are directly connected with the qualified personnel potential of a higher educational establishment, level of educational and methodical and computer and technical provision, availability of a proper library and a manifold infrastructure. It identifies basic principles and priorities of development of a higher educational establishment in the field of introduction of information and network technologies and forms a long-term programme of informatisation. It specifies its main tasks: development and improvement of educational and scientific information and communication environment of a higher educational establishment, provision of effective and high quality training of specialists and integration of a higher educational establishment into the national and world system of education. The study of quantitative and qualitative indicators of realisation of a complex programme of informatisation testifies to importance of the innovation component in activity of a higher educational establishment. The further study of the information and educational environment of a higher educational establishment is directed at establishment of a connection with the quality of educational process, effectiveness of scientific studies? managerial and innovation activity. В статье исследованы факторы конкурентоспособности образовательного учреждения: востребованность специальностей, их популярность и стоимость обучения. Проведенный анализ показал, что эти факторы напрямую связаны с квалифицированным кадровым потенциалом вуза, уровнем учебно-методического и компьютерно-технического обеспечения, наличием полноценного библиотечного фонда, разветвленной инфраструктурой. Определены основополагающие принципы и приоритеты развития вуза в области внедрения информационных и сетевых технологий, сформирована долгосрочная программа информатизации. Выделены ее основные задачи: развитие и совершенствование образовательной и научной информационно-коммуникационной среды вуза, обеспечение эффективной и качественной подготовки специалистов, интеграция вуза в национальную и мировую систему образования. Изучение количественных и качественных показателей реализации комплексной программы информатизации свидетельствует о важности инновационной составляющей в деятельности вуза. Дальнейшее изучение информационно-образовательной среды вуза направлено на установление связи с качеством учебного процесса, эффективностью научных исследований, управленческой и инновационной деятельности.